Prevalence and prognostic significance of malnutrition in patients with cancers of the head and neck. Issue 3 (March 2020) - Kubrak, Catherine; Martin, Lisa; Gramlich, Leah; Scrimger, Rufus; Jha, Naresh; Debenham, Brock; Chua, Neil; Walker, John; Baracos, Vickie E.
Summary: Background & aims: Head and neck cancer (HNC) are at high nutritional risk; however the prevalence and severity of malnutrition in contemporary patients with HNC are unclear. Diagnostic criteria for cancer-associated weight loss grading (WLG) (Grades 0 to 4) [1] have been validated and are recommended in oncology nutrition clinical practice guidelines [2–3]. The aim was to determine the prevalence using WLG in HNC patients and determine the extent to which reduced dietary intake (DI) explained variation of WLG. Methods: A population-based cohort of HNC patients (N = 1756) in northern Alberta, Canada included consecutive new patients, 2004–2016. At referral to the regional cancer center weight history and DI categories were collected. Multinomial logistic regression (MLR) identified predictors of weight loss (WL) severity. Overall survival (OS) in relation to WL Grade and DI was determined by multivariable Cox proportional hazard. Results: WL was absent in 42.9% and the remainder had Grade 1 (18%), Grade 2 (14.7%), Grade 3 (15.9%) and Grade 4 (8.5%) WL. Independent predictors of WLG in adjusted MLR model, included stage (P < 0.000), performance status (PS) (P < 0.000) and DI categories (P < 0.000); sex, age and disease site were not significant. Compared to "normal food in normal amount" adjusted Odds Ratio for WL Grade 4 was 4.0 (2.1–7.5) "normal food, but less than normal amount"; 25.2 (10.7–59.1) "little solid food"; 51.8 (10.5–255.3) "very little of anything"; 42.4 (11.0–163.0) "only liquids"; 25.9 (7.1–94.3) "only nutritional supplements". In the Cox model controlled for age, sex, cancer stage and site and PS, both WLG ((P < 0.000) and DI categories (P = 0.003) independently predicted OS. Conclusion: Data from this population cohort provide a benchmark for prevalence of cancer associated WL severity at diagnosis. Patient reported DI categories are strong predictors of WL and prognostic for OS. Highlights: Population-based cohort of head and neck patients (HNC) (N = 1756) in Alberta, Canada. Weight loss (WL) absent in 42.9%, but WL present in 57% of new HNC referrals. Predictors of WL included stage, dietary intake and performance status (P < 0.000). WL Grade ((P < 0.000) and Dietary intake (P < 0.003) independently predicted survival. WL history and dietary intake have high clinical utility in clinical practice.